P109. Parietofrontal motor pathways and their association with motor function after stroke. Issue 8 (August 2015) - Koch, P.; Schulz, R.; Zimerman, M.; Wessel, M.; Bönstrup, M.; Thomalla, G.; Cheng, B.; Gerloff, C.; Hummel, F.C.
<x xml:space="preserve">Abstract</x> Background A stroke results in widespread alterations of motor-related brain activity and interregional interactions in the sensorimotor network. Numerous studies have investigated the functional relevance of the primary motor cortices (M1) and predominantly frontal and prefrontal secondary motor areas. Only few studies focused on the functional role of the ventral premotor cortex (PMv) and the posterior parietal cortex (PPC) after stroke. Corticocortical interactions between M1, PMv and posterior parietal motor areas, such as the anterior (aIPS) and caudal intraparietal sulcus (cIPS) are relevant for skilled voluntary hand function. It remains unclear to what extent these brain regions and their interactions also contribute to rather basic motor functions after stroke. We hypothesized that the white matter integrity of the underlying parietofrontal motor pathways between these brain regions might relate to residual motor function after stroke. Methods 25 chronic stroke patients (aged 64 ± 8.8 years, 17 male, 1 left-handed) with a broad spectrum of first-ever cortical and subcortical ischemic strokes were evaluated by means of grip force, pinch force and the Fugl-Meyer score. Principal component analysis was used to calculate one composite motor function score (MF). Diffusion tensor imaging and probabilistic tractography were used to reconstruct probable intrahemispheric trajectories between M1, PMv, aIPS and cIPS in each patient. Tract-related white matter integrity was estimated by means of fractional anisotropy (FA). Generalized linear modeling was used to correlate tract-related FA values with MF. Results We found that the FA values of the fiber tracts connecting PMv and M1 (p < 0.05) and also aIPS and PMv (p < 0.05) showed a positive correlation with recovered motor function of the paretic hand. The other tracts investigated did not show a similar structure–behavior association. Conclusion This indicates that the ventral premotor cortex and the posterior parietal cortex, and the structural integrity of their connections within the motor network are crucially involved in recovered motor function after stroke.